Konsep, Teori, Dan Komponen-Komponen Pengembangan Kurikulum Pendidikan Bahasa Arab - Anwar Abd. Rahman; Miftahul Jannah; Surya Verbena Sukarman; A. Razma Aula Adhzara; Ainul Maksura (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2026)
Curriculum is an essential component of the educational system that functions as a guideline in designing, implementing, and evaluating the learning process. In Arabic Language Education, the curriculum is not only oriented toward mastering linguistic materials but also toward developing the four language skills: listening (istimāʿ), speaking (kalām), reading (qirāʾah), and writing (kitābah). This article aims to examine the basic concepts of curriculum, theories of curriculum development, and the main components of the Arabic Language Education curriculum. This study employs a descriptive qualitative approach using the library research method. Data were collected from books, scientific journals, and relevant educational documents, then analyzed using content analysis techniques. The findings indicate that curriculum theories proposed by Bobbitt, Caswell, Ralph Tyler, Hilda Taba, and Hamid Hasan provide significant contributions to the development of a more contextual, communicative, and adaptive Arabic language curriculum in response to contemporary educational needs. In addition, curriculum components consisting of objectives, materials, methods and media, as well as evaluation, are closely interconnected in creating effective Arabic language learning. This article offers novelty through the integration of curriculum theories with modern Arabic language learning practices that are technology-based, communicative, and student-centered. Therefore, the development of the Arabic language curriculum is expected to produce a more relevant, innovative, and contextual learning process in accordance with the demands of contemporary education